2018
DOI: 10.1002/slct.201801955
|View full text |Cite
|
Sign up to set email alerts
|

A General and Simple Method of Preparing Molybdenum‐ Incorporated Silica Nanoparticles as Potential Catalysts for Epoxidation of Alkenes

Abstract: Molybdenum incorporated silica nanoparticles were synthesized by a general and simple method and developed as efficient catalysts for epoxidation of alkenes with high performance. The nanoparticles were prepared in mild conditions with cetyltrimethyl ammonium bromide as template, tetraethyl orthosilicate as silica source and triethanolamine as mineralizing agent. Molybdenum precursor was added during the sol‐gel process and transferred to active sites MoO3 after calcination. Remarkably, the shape of silica nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, the porosity of silica-based materials also contributes to restrict the size of molybdenum species and to achieve MoO x species in high dispersion. We [76] used this route to incorporate molybdenum species in silica nanoparticles and obtained molybdenum incorporated silica nanoparticles. These catalysts have been used in epoxidation of alkenes and obtained efficient reactivity.…”
Section: Silica Supported Molybdenum-based Catalystsmentioning
confidence: 99%
“…Moreover, the porosity of silica-based materials also contributes to restrict the size of molybdenum species and to achieve MoO x species in high dispersion. We [76] used this route to incorporate molybdenum species in silica nanoparticles and obtained molybdenum incorporated silica nanoparticles. These catalysts have been used in epoxidation of alkenes and obtained efficient reactivity.…”
Section: Silica Supported Molybdenum-based Catalystsmentioning
confidence: 99%
“…On the other hand, the modication of methods comprises the development of processes by using alternative energy resources or improvement of yield with synergistic effects such as mixing program, 22 ultrasonic irradiation, 47,62 microwave technology, [81][82][83][84][85][86][87] high temperature, 88 and hydrodynamic cavitation. 89 Our group has studied amphiphilic phosphotungstatepaired ionic copolymer 90 and molybdenum-based catalysts [91][92][93][94][95][96][97][98] on various supports for the epoxidation of different alkenes and good results were obtained. Moreover, recent developments in the application of molybdenum-based catalysts for epoxidation have been reviewed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the involvement of morphology-controlled silica incor-porating/embedding molybdenum oxide nanoparticles (NPs) have been developed; for example, monodispersed SiO2 spheres embedding MoO3 nanoparticles prepared with Brij-58/cyclohexane/water reverse micro-emulsions have been presented by Wang et al [28]. Spherical MoO3@SiO2 nanoreactors prepared via impregnation of hollow mesoporous silica spheres (HMSS) and rose-like molybdenum incorporated silica nanoparticles have been recently reported by Shen et al [29,30]. Recent work by Gu et al has demonstrated MoO3 nanoparticles in 3D dendritic mesoporous silica nanospheres [31].…”
Section: Introductionmentioning
confidence: 99%